MAKING FERTILIZER AND PEST REPELLENT FROM EGG SHELLS IN LAMCEU VILLAGE, ACEH BESAR REGENCY: PEMBUATAN PUPUK DAN PENANGKAL HAMA DARI CANGKANG TELUR DI DESA LAMCEU KABUPATEN ACEH BESAR - Mizar Liyanda; Sri Agustina; Aprita, Ika Rezvani; Yusran Akbar; Endiyani; Dewi Yana; Stevelint Ayu Rizki (WISDOM : Jurnal Pengabdian Kepada Masyarakat Wisdom, 2025)
The goal of the PKM activity is to broaden the understanding and insight into the social life of the people of Gampong Lamceu, Aceh Besar Regency, on utilizing chicken eggshell waste in organic fertilizer and pest control. The implementation of PKM aims to use natural resources and surrounding waste, with the hope of improving the community's economy. This PKM activity involves lecturers and students of Politeknik Indonesia Venezuela to explore the potential and conditions in Gampong Lamceu. The implementation of Community Service activities uses a two-stage method. First, providing material to the community and explaining the techniques for making fertilizers and pest control from eggshells, then followed by discussion and questions and answers about the manufacturing process. The second stage is to practice directly in front of the villagers. The steps for making fertilizer and pest repellent from eggshells in the Community Service activity are as follows: preparing tools and materials for practice, including eggshell waste and water for the sterilization process. The water is heated to boiling, then the eggshells are put in and allowed to stand for 5 minutes. After drying, the eggshells are crushed using a blender and are ready to be used to support plant growth and as a pest repellent. From the implementation of the Community Service Program in Lamceu Village, it can be concluded that the community is very happy and enthusiastic about the activities carried out by lecturers and students of the Indonesian Polytechnic of Venezuela. The community has understood how to make fertilizers and pest repellents from eggshell waste and can develop their potential to be more creative in creating new things.